PERILAKU STRUKTUR LANTAI PSSDB (PROFILED STEEL SHEET DRY BOARD) DENGAN LUBANG BULAT DITENGAH - Muhammad Yazid (Racic : Rab Construction Research, 2019)
The knowledge on the behaviour of a building structure is very important in order to predict the behaviour of the structure before it is constructed. This is to ensure that the structure is safe to be used. New current modern technology is now able to predict the behaviour of a structure through computer simulation as a replacement to laboratory tests. However, laboratory tests will also have to be performed in order to validate the proposed computer models. This thesis illustrates the prediction of the structural behaviour of Profiled Steel Sheet Dry Board (PSSDB) which is a structural composite floor system constructed of Bondek II (profiled steel sheeting), Cemboard (dry board) connected via Power Drive DX14 (self drilling, self tapping screws). The floor structure is loaded with a uniformly distributed loading and its behaviour due to the openings at the center of the panel analysed using a finite element perangkat lunak package, LUSAS-FE. The one-way spanning plate have been analysed in this research. The increase in deflection in the longitudinal direction is found to be more influenced by the presence of the opening than the deflection in the transverse direction. The average percentage of the increase in deflection of the one-way spanning plate due to the presence of 20%, 40%, and 60% opening of its overall width are 36%, 108%, and 184% respectively in comparison to the deflection of plate without opening. It has been found that as the size of opening increases, the deflection also increased.